PENERAPAN REAKTOR BIOGAS FIXED DOME DALAM PENGOLAHAN LIMBAH PETERNAKAN MENJADI SUMBER ENERGI TERBARUKAN DI DESA BRAJAN, BOYOLALI - Ariastuti, Reni; Qonitah, Fadilah; Indriastiningsih, Erna; Widagdo, Arisena; Nabila, Jihan (Universitas Padjadjaran, 2025)
The potential natural resources of Brajan Village, Mojosongo, Boyolali include the availability of fertile rice fields covering an area of 166.651 hectares, almost 60% of the total area. Residents utilize this potential for farming and animal husbandry. These activities produce various kinds of waste, including post-harvest waste and livestock manure. The waste produced is generally unused or disposed of by residents. Starting from the large amount of existing potential, Sahid University Surakarta held community service activities aimed at reducing environmental pollution caused by untreated waste, as well as making the waste more useful and economically valuable. This activity was carried out by constructing a fixed dome biogas reactor and continued with training on the application of using the reactor to process livestock manure into biogas and organic compost from bio-slurry. In this service activity, the team provided a biogas reactor installation to one of the Brajan Village residents as a grant recipient. In addition, support in the form of chopping machines and agricultural tools was also provided to Gapoktan members as farming and composting equipment. Training activities were also conducted to increase the knowledge of Brajan Village residents regarding biogas and compost. This community service activity was considered successful and well-targeted because, after participating in the training, the residents' knowledge level regarding biogas and compost, which was initially classified as fair, improved to a very good level. Moreover, agricultural and livestock waste that was previously discarded now has higher economic value because it can be processed into biogas and compost. Potensi sumber daya alam Desa Brajan, Mojosongo, Boyolali berupa ketersediaan lahan persawahan subur seluas 166,651 Hektar, hampir 60% dari luas total wilayah. Potensi tersebut dimanfaatkan warga untuk bertani dan berternak, dari aktivitas tersebut menghasilkan berbagai macam limbah, diantaranya limbah pasca panen dan kotoran ternak. Limbah yang dihasilkan pada umumnya tidak dimanfaatkan/dibuang oleh warga. Berawal dari banyaknya potensi yang ada, Universitas Sahid Surakarta mengadakan kegiatan pengabdian yang bertujuan untuk mengurangi pencemaran lingkungan akibat limbah yang tidak tertangani, serta menjadikan limbah lebih bermanfaat dan bernilai ekonomis. Kegiatan ini dilakukan dengan pembuatan reaktor biogas teknologi fixed dome dan dilanjutkan pelatihan aplikasi penggunaan reaktor dalam mengolah kotoran ternak menjadi biogas dan komos organik dari bio-slurry. Pada kegiatan pengabdian ini, tim pengabdi memberikan instalasi reaktor biogas kepada salah satu warga Desa Brajan sebagai penerima hibah. Selain itu bantuan berupa mesin pencacah dan alat pertanian juga diberikan kepada anggota gapoktan sebagai sarana bertani dan membuat kompos. Kegiatan pelatihan juga dilakukan untuk meningkatkan pengetahuan warga Desa Brajan terkait biogas dan kompos. Kegiatan pengabdian ini dinilai berhasil dan tepat sasaran karena setelah mengikuti pelatihan tigkat pengetahuan warga terkait biogas dan kompos yang awalnya tergolong cukup menjadi sangat baik. Di samping itu, limbah pertanian dan peternakan yang dibuang begitu saja sekarang menjadi lebih bernilai ekonomis karena mampu diolah menjadi biogas dan kompos.